(untitled) (ModaPalavra e-periódico, 2016)
The trend indicates that an increase in the consumption of apparel goods leaving the generated comfort motivates its use in this study, which proposes understand to factors that assits the construction of traditional clothes strengthening links with ergonomics and providing positive use experience. By understanding that, about ergonomics, the full satisfaction of the costumers before a product occurs between it technical adequacy, ergonomic and aesthetic, that provides opportunities for development of new solutions in the construction of these garments. This search involves the application of concepts for further development of the form in order to encourage the pursuit of satisfaction of users towards fashion products, in view of its importance in differentiation from similar already on the market as well as the statement brands with values geared towards concern for the well being of their customers.